Pre-operative nutrition assessments do not improve outcomes in cerebral palsy patients undergoing varus derotational osteotomy. Issue 47 (24th November 2021) - Obana, Kyle K.; Fan, Bensen B.; Bennett, James T.; Lin, Adrian; Goldstein, Rachel Y.; Andras, Lindsay M.; Kay, Robert M.
Abstract : Abstract: Pre-operative nutritional assessments have been used as a "cornerstone" to help optimize nutritional status and weight in children with cerebral palsy (CP) to lower the risk of postoperative complications. However, the potential value of nutritional assessments on surgical outcomes in patients with CP undergoing major orthopedic surgery remains unproven. Do pre-operative nutritional assessments reduce complication rates of varus derotational osteotomy surgery in children with CP? Are complication rates higher in patients with a gastrostomy tube (G-tube) and can they be decreased by pre-operative nutritional assessment? One-hundred fifty-five patients with CP who underwent varus derotational osteotomy from January 1, 2012 through December 31, 2017 at a tertiary pediatric hospital with minimum 6 months follow-up were retrospectively identified. One-hundred-ten (71%) were categorized as "non-ambulatory" (Gross Motor Function Classification System [GMFCS] IV–V), and 45 (29%) as "ambulatory" (GMFCS I–III). Variables assessed included age, GMFCS level, G-tube, body mass index (BMI) percentile, complications, and if patients underwent pre-operative nutritional assessment. One-hundred-eleven patients (71.6%) underwent pre-operative nutritional assessment. Sixty-two of 155 patients (40.0%) had G-tubes. In non-ambulatory patients with G-tubes, BMI percentile changes were not significantly different between patients with a pre-operative nutritional assessment compared to those without at 1 ( P  = .58), 3 ( P  = .61), 6 ( P  = .28), and 12 months ( P  = .21) postoperatively. In non-ambulatory patients who underwent pre-operative nutritional assessment, BMI percentile changes were not significantly different between those with and without G-tubes at 1 ( P  = .61), 3 ( P  = .71), 6 ( P  = .19), and 12 months ( P  = .10). Pulmonary complication rates were significantly higher in non-ambulatory patients with G-tubes than in non-ambulatory patients without G-tubes (20% vs 4%, P  = .03). Pre-operative nutritional assessments did not influence postoperative complication rates for non-ambulatory patients with or without a G-tube ( P  = .12 and P  = .16, respectively). No differences were found in postoperative complications between ambulatory patients with and without G-tubes ( P  = .45) or between ambulatory patients with or without nutritional assessments ( P  = .99). Nutritional assessments, which may improve long term patient nutrition, should not delay hip surgery in patients with CP and progressive lower extremity deformity. Patients and their families are unlikely to derive any short-term nutritional improvement using routine pre-operative evaluation and surgical outcomes are unlikely to be improved. Level of Evidence: III, retrospective comparative.